The applicability of gaming simulation in teaching and learning in urban and regional planning: a ten-year case study at the University of the Free State - Barclay, Elizabeth (University of the Free State, 2013)
Abstract not available
Thesis (Ph.D. (Urban and Regional Planning))--University of the Free State, 2012
Keywords: City planning -- Study and teaching (Higher) -- Simulation methods; Regional planning -- Study and teaching (Higher) -- Simulation methods; Simulation games in education; Simulation environment (Teaching method); Simulation methods